IDENTITAS PRA-INDONESIA DALAM CERITA-CERITA PRA-INDONESIA - Pujiharto Pujiharto; Wening Udasmoro; Mutiah Amini (LITERA, 2014)
This study aims to describe characterization of pre-Indonesian characters and therelationship between characterization patterns and the process of the appearance of pre-Indonesian identities in pre-Indonesian stories. The data sources were stories entitled: (1)“Busono” by Raden Mas Tirto Adhi Soerjo, (2) “Tjerita Si Tjonat” by F.D.J. Pangemanan,(3) “Tjerita Njai Dasima” by G. Francis, (4) “Tjerita Njonja Kong Hong Nio” and (5)“Tjerita Nji Paina” by H. Kommer. Several concepts to answer the problems were pre-Indonesian identities, characterization, and focalization. The findings are as follows. First,characters in pre-Indonesian stories and the relationship with pre-Indonesian identitiesshow that some are self-aware and some are not. Second, the existence of characters inpre-Indonesian stories with characterization shows that pre-Indonesian identities havea relationship with the authors’ focalization.